Status of the XENON Project. Issue 4 (May 2016) - Garbini, Marco
Abstract: Astronomical and cosmological observations indicate that a large amount of the energy content of the Universe is made of dark matter. The most promising dark matter candidates are the so-called Weakly Interacting Massive Particles. The search for these particles is performed with various experimental approaches. The XENON Project, at the Gran Sasso National Laboratory, is devoted to the direct search of dark matter particles. It consists in operating a double-phase time projection chamber using ultra-pure liquid Xenon as both target and detection medium for dark matter particle interactions. The WIMPs can be indeed detected via their elastic scattering off Xenon nuclei. The XENON100 detector with 160 kg of liquid Xenon has reached in 2012 the sensitivity of 2×10 -45 cm 2 at 55 GeV/ c 2 and 90% confidence level on spin-independent elastic WIMP-nucleon scattering cross section. The next generation XENON1T detector, that will host 3.3 tonnes of ultra-pure liquid Xenon, is in its final stage of construction and will likely start taking data by the end of 2015. The detector is designed to increase the sensitivity by two orders of magnitude.